Controlling Metallophilic Interactions in Chiral Gold(I) Double Salts towards Excitation Wavelength‐Tunable Circularly Polarized Luminescence - Yang, Jian‐Gong; Li, Kai; Wang, Jian; Sun, Shanshan; Chi, Weijie; Wang, Chao; Chang, Xiaoyong; Zou, Chao; To, Wai‐Pong; Li, Ming‐De; Liu, Xiaogang; Lu, Wei; et al. (Angewandte Chemie International Edition, 2020)
Materials exhibiting excitation wavelength‐dependent photoluminescence (Ex‐De PL) in the visible region have potential applications in bioimaging, optoelectronics and anti‐counterfeiting. Two multifunctional, chiral [Au(NHC)2][Au(CN)2] (NHC=(4R,5R)/(4S,5S)‐1,3‐dimethyl‐4,5‐diphenyl‐4,5‐dihydro‐imidazolin‐2‐ylidene) complex double salts display Ex‐De circularly polarized luminescence (CPL) in doped polymer films and in ground powder. Emission maxima can be dynamically tuned from 440 to 530 nm by changing the excitation wavelength. The continuously tunable photoluminescence is proposed to originate from multiple emissive excited states as a result of the existence of varied AuI⋅⋅⋅AuI distances in ground state. The steric properties of the NHC ligand are crucial to the tuning of AuI⋅⋅⋅AuI distances. An anti‐counterfeiting application using these two salts is demonstrated. Ex‐De CPL: By modulating the strength of AuI⋅⋅⋅AuI and Coulombic interactions by adjusting steric hindrance of the ligand, together with the materials processing, the two chiral enantiomers of [Au(NHC)2][Au(CN)2] double salts in PMMA film or as ground powder exhibit mirror‐image excitation wavelength‐dependent photoluminescence (Ex‐De CPL).